Hubungan Motivasi dengan Hasil Belajar IPA Siswa Selama Pembelajaran Tatap Muka Terbatas - Meri, Meri; Enawaty, Enywaty; Masriani, Masriani; Muharini, Rini; Ulfah, Maria (Hydrogen: Jurnal Kependidikan Kimia, 2022)
Limited face-to-face learning (PTMT) has been carried out but theÂ implementation of the learning process which lasts 30 minutes for one meeting inÂ learning makes the teacher only convey essential material. Face-to-face learningÂ is more effective than online learning. Motivation is one of the important factorsÂ in the success of a learning. This study aims (1) to determine the science learningÂ motivation of class VIII students of SMPN 4 Pontianak even semester 2021-2022Â during PTMT, (2) to determine the relationship between learning motivation andÂ science learning outcomes for class VIII students at SMPN 4 Pontianak evenÂ semester 2021-2022 during PTMT. The research subjects were students of classÂ VIII SMPN 4 Pontianak. The research method is descriptive with a quantitativeÂ approach. Science learning outcomes are obtained from the average dailyÂ science test scores of students. This research is a descriptive research with aÂ quantitative approach. Data collection techniques use direct, indirect, andÂ documentation communication. Descriptive statistics were used as a dataÂ analysis technique. The results showed that the average learning motivation wasÂ 70.81% while the percentage of learning outcomes was 81.4%. Both motivationÂ and learning outcomes are included in the high category. The results of theÂ Â Spearman’s Rho test between science learning motivation and science learningÂ outcomes obtained (r = 0.019) < ( r = 0.05) which means that there is aÂ relationship between motivation and science learning outcomes for SMPN 4Â Pontianak students, namely the higher the motivation, the higher the studentÂ learning outcomes. the higher it is. The results of this study can be concludedÂ that the science learning motivation of SMPN 4 Pontianak students in the evenÂ semester of 2021-2022 is high with a percentage of 70.81%. There is aÂ significant and positive relationship between learning motivation and learningÂ outcomes for science students of class VIII SMPN 4 Pontianak even semesterÂ 2021-2022 during PTMT.